William Pitt Fessenden papers - Fessenden, William Pitt, 1806-1869.
Correspondence with related clippings and printed material pertaining chiefly to Fessenden's service on the U.S. Senate Committee on Finance and as U.S. secretary of the treasury under Abraham Lincoln. Subjects include Maine and national politics, disputed territorial claims in Maine, abolitionism, operations of the Treasury Dept. in 1864 and 1865, financing the Civil War, financial crises in the U.S. during the 1860s, Reconstruction, the impeachment of Andrew Johnson, and Fessenden's personal and family affairs.
Correspondents include Elisha Hunt Allen, John Birney, Gamaliel Bradford, John J. Cisco, Nathaniel Dale, Timothy Davis, Hamilton Fish, A. T. Galt, R. M. Griffin, Morris Ketchum, Hugh McCulloch, Robert A. Maxwell, Freeman H. Morse, William D. Porter, John A. Stewart, George M. Towle, Joseph A. Ware, and J. E. Williams.
Microfilm edition of volumes 1-8 available
Microfilm produced from originals in the Manuscript Division.
U.S. secretary of the treasury, U.S. senator and representative from Maine, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allen, Elisha Hunt, -- 1804-1883 -- Correspondence; Birney, John -- Correspondence; Bradford, Gamaliel, -- 1831-1911 -- Correspondence; Cisco, John J. -- Correspondence; Dale, Nathaniel -- Correspondence; Davis, Timothy, -- 1821-1888 -- Correspondence; Fish, Hamilton, -- 1808-1893 -- Correspondence; Galt, A. T. -- Sir, -- 1817-1893 -- Correspondence; Griffin, R. M. -- Correspondence; Johnson, Andrew, -- 1808-1875 -- Impeachment; Ketchum, Morris, -- active 1864 -- Correspondence; McCulloch, Hugh, -- 1808-1895 -- Correspondence; Maxwell, Robert A. -- Correspondence; Morse, Freeman H. -- 1807-1891 -- Correspondence; Porter, Wm. D. -- 1810-1883 -- Correspondence; Stewart, John Aikman, -- 1822-1926 -- Correspondence; Towle, George M. -- 1841-1893 -- Correspondence; Ware, Joseph A. -- Correspondence; Williams, J. E. -- Correspondence; Fessenden family; United States. -- Congress. -- Senate. -- Committee on Finance; United States. -- Department of the Treasury. -- Office of the Secretary; Antislavery movements -- United States; Financial crises -- United States -- History -- 19th century; Reconstruction (U.S. history, 1865-1877); Slavery; Great Britain -- Foreign relations -- United States; Maine -- Politics and government; Northeast boundary of the United States; United States -- Economic policy -- To 1933.; United States -- Foreign relations -- Great Britain; United States -- History -- Civil War, 1861-1865 -- Finance; United States -- Politics and government -- 19th century; Cabinet officers; Lawyers; Representatives, U.S. Congress -- Maine; Senators, U.S. Congress -- Maine